STUDI PENGETAHUAN GURU PJOK TERHADAP PELAKSANAAN P3K PADA SISWA SEKOLAH DASAR NEGERI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Farras Naufal; Agus Sulastio; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem of this research is that there is still a lack of knowledge of teachers of Physical Health Sport Education (PJOK) Elementary School Rumbai Pesisir Pekanbaru City on knowledge of the implementation of P3K on injuries during learning to students. The aim is to find out how far the educational background and knowledge of PJOK teachers are in tackling and dealing with accidental injuries in State Elementary School students, Rumbai Pesisir District, Pekanbaru City with the implementation of first aid. This type of research is quantitative descriptive with survey method. the instrument used in the form of a questionnaire or questionnaire. The data analysis technique used a descriptive percentage technique. The population in this study amounted to 20 people in 20 schools, of which 10 PJOK teachers were taken to be the research sample from 10 public elementary schools in Rumbai Pesisir sub-district. The sampling technique used is the simple random sampling technique, namely by pulling the lottery without any prejudice. To measure the validity of the research tool or instrument, the product moment correlation test technique from Karl Pearson was used with a significant level of 5% or 0.05, then analyzed with the help of SPSS 26 research instruments were said to be valid if (Rcount Rtable). The R table value for respondent 10 is (0.632) if the result of Rcount is greater than (0.632) then the item of the instrument is said to be valid. Of the 48 statement items, there are 3 items whose Rcount value is less than (0.632) namely statement items 33, 36 and 41. The results of the Rcount for item 33 are (0.617), Rcount for item 36 is (0.530), while item 41 Rcount is (0.541 ) which is greater than or equal to Rtable (0.632). The results showed that the teacher's knowledge in the implementation of First Aid to State Elementary School students, Rumbai Pesisir sub-district, Pekanbaru City in 2020/2021 was included in the medium category. With a percentage of 0.00% included in the Very Good category, 30.00% included in the Good category, 50.00% included in the Medium category, 10.00% of in the Less category and 10.00% is included in the Once less category. Keywords: Knowledge and Implementation of First Aid in Elementary School Students